First WHO/UNEP survey of the current concentrations of persistent organic pollutants in human milk in Morocco. Issue 2 (1st February 2023) - Ait lhaj, Farida; Elhamri, Hecham; Ait lhaj, Zakaria; Malisch, Rainer; Kypke, Karin; Kabriti, Mohamed; El Hajjaji, Souad; Bellaouchou, Abdelkabir
Abstract: The presence of persistent organic pollutants (POPs) in human milk is an indicator of the level of these substances in the environment and enables evaluation of the potential exposure of breastfed children. POPs concentrations in a Moroccan human milk pooled sample (59 donors) were determined for the first time by the WHO reference laboratory to provide a baseline and allow monitoring of the future trends for those persistent organohalogen compounds. Eighty-one different POPs, including organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs), and dioxins and furans (PCDD/Fs) were identified and quantified by using gas chromatography (GC) with an electron capture detector (ECD) and confirmed by gas chromatography-mass spectrometry (GC/LRMS). The obtained results showed that the sum of DDT (sum of o, p'-DDD, p, p′-DDD, o, p′-DDE, p, p′-DDE, o, p'-DDT, and p, p′-DDT) was 237.9 ng/g, representing 94.0% of all detected OCPs levels, with a dominance of p, p′-DDE, and p, p′-DDT. Cis-heptachlor epoxide, HCB, and HCH were found at much lower levels. PCB indicator level was 60.7 ng/g of lipid, with the dominance of PCB 138, PCB 153, and PCB 180, presenting 98.3% of the total. Among the 25 PBDE congeners quantified, BDE-47, BDE-153, BDE-197, and BDE-207 were the dominant congeners account for 15.4% of the total concentration of PBDE (1.3 pg/g lipid). The lipid-adjusted level of PCDD/Fs and dl-PCBs expressed in Toxic Equivalents (TEQs: 6.65 pg/g) were lower in comparison to those found in the other countries. In summary, detected POPs levels in Moroccan human milk were much lower compared to the other countries, reflecting the effectiveness of the compliance with Stockholm Convention requirements on eliminating or reducing emissions of selected POPs. Continued monitoring is needed for these compounds, for which this is the first data available, provided by the WHO/UNEP survey in Morocco.